2019
DOI: 10.1142/s0129055x20500105
|View full text |Cite
|
Sign up to set email alerts
|

The Landau Hamiltonian with δ-potentials supported on curves

Abstract: The spectral properties of the singularly perturbed self-adjoint Landau Hamiltonian Aα = (i∇ + A) 2 + αδΣ in L 2 (R 2 ) with a δ-potential supported on a finite C 1,1 -smooth curve Σ are studied. Here A = 1 2 B(−x2, x1) ⊤ is the vector potential, B > 0 is the strength of the homogeneous magnetic field, and α ∈ L ∞ (Σ) is a position-dependent real coefficient modeling the strength of the singular interaction on the curve Σ. After a general discussion of the qualitative spectral properties of Aα and its resolven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…(3.9) It is well known that Φ λ and C λ are bounded and everywhere defined and that 11) and this operator is also bounded when viewed as an operator from L 2 (Ω; C 4 ) to H 1/2 (∂Ω; C 4 ); cf. [12, equation (2.12) and the discussion below].…”
Section: Integral Operatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3.9) It is well known that Φ λ and C λ are bounded and everywhere defined and that 11) and this operator is also bounded when viewed as an operator from L 2 (Ω; C 4 ) to H 1/2 (∂Ω; C 4 ); cf. [12, equation (2.12) and the discussion below].…”
Section: Integral Operatorsmentioning
confidence: 99%
“…For that, we use the following result on operators with range in the Sobolev space . Its proof follows word-by-word the one of [ 11 , Proposition 2.4]; hence, we omit it here.…”
Section: The Minimal the Maximal The Mit Bag And Some Associated Imentioning
confidence: 99%
See 1 more Smart Citation
“…the singular interaction does not have an effect on u, and hence H υ u = H 0 u = Λ q u. This allows one to show with the help of [7,Lemma 3.7] that the kernel of T q (υδ Γ ) is finite-dimensional under the assumption that υ is strictly positive. Moreover, this connection provides a direct link to nodal sets for eigenfunctions of H 0 and the non-emptiness of ker (H υ − Λ q ).…”
Section: Introductionmentioning
confidence: 95%
“…In the spectral gaps (Λ q−1 , Λ q ), where q ∈ Z + and Λ −1 := −∞, of H 0 there may appear discrete eigenvalues of H υ which can only accumulate at the Landau levels Λ q , q ∈ Z + . Some results on the asymptotic distribution near any fixed Λ q of these discrete eigenvalues were obtained in [7]. In particular, it was shown that if either υ ≥ 0 or υ ≤ 0 on Γ, v ≡ 0, and certain additional regularity assumptions hold, then in a neighbourhood of any Λ q there are infinitely many discrete eigenvalues of H υ and their accumulation rate to the Landau levels is described in terms of the logarithmic capacity of the interaction support; cf.…”
Section: Introductionmentioning
confidence: 99%